Data Protection in Social Services : A Comprehensive Guide to HIPAA and GDPR Implementation - Nanda Kishore Chevuri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Data security and privacy regulations play a pivotal role in shaping the integration landscape of social services systems. This technical article explores the comprehensive implementation of security measures and compliance frameworks, focusing on HIPAA and GDPR requirements in social services integration. It examines encryption protocols, access control mechanisms, and audit capabilities while providing practical guidelines for maintaining regulatory compliance. By analyzing the technical architecture, implementation strategies, and ongoing maintenance requirements, this article offers insights into building robust, secure, and compliant integration solutions that protect sensitive personal information while enabling efficient service delivery across social service organizations.